The Gut Mucosal Microbiome of HIV- exposed Uninfected Infants in Africa - Khomunala, Phumudzo (Division of Chemical and Systems Biology, 2021)
Background: South Africa has a large HIV disease burden, with the highest rate of infection occurring in young women of the childbearing age. This gave impetus to the Prevention-of-Mother-To-Child-Transmission (PMTCT) program, that has been successfully implemented. Due to the success of the PMTCT program, HIVexposed-uninfected (HEU) infants represent a growing population in South Africa. However, these infants have been found to have increased morbidity and mortality rates compared to their HIV Unexposed Uninfected (HUU) peers, as well as altered immune and vaccine responses. The reasons for this remain unclear, but one hypothesis is that altered gut microbiomes in HEU adversely affect the developing infant immune system. The microbiome (a collection of an array of microorganisms, their genes, genomes, proteomes, and metabolites) is an area of emerging research interest; dysbiosis of the gut microbiome has recently been associated with disease outcomes and progression in several disease areas. The microbial colonisation of the infant begins in utero and continues after birth. It is affected by several factors: birth mode, age of gestation, feeding mode, maternal health status as well as environmental factors. Aim: To elucidate the microbiomes of HEU infants in Africa, compared to HUU controls Design: Ultra-high-performance liquid chromatography mass spectrometry was used to analyse and characterize a subset of existing stool samples stored from the InFANT cohort study. The infant gut metaproteome of 34 HEU versus 29 HUU infants, from the South African arm of the study was analysed. Cross-sectional samples were collected and analysed at two-time points, namely at birth and within the first week of life (between 4 to 7 days after birth). Results: Comparative analysis of the HEU and HUU reveal differences in the microbial composition between the two groups at birth and day 4-7, with the most apparent difference occurring at birth. In our comparison we found that the relative abundances of Bacteroidetes and Firmicutes were different between the HEU and HUU at both birth and day 4-7. There was a dramatic shift in the microbial composition within the first week of life. Conclusion: It is evident from our analysis that the HEU infant has a different gut microbiome to that of the HUU infant at birth. The HEU microbiome is characterised by a high microbial diversity at birth. This could be associated with more severe outcomes from childhood ailments. The human breast milk (HBM) microbiome greatly influences and mitigates the differences upon subsequent breastfeeding, but differences in the measured microbiomes of HEU and HUU nonetheless remain. Recommendations: A longitudinal study should be carried out to better monitor the long-term effects of the microbiome on infant immune priming. A study of the HBM microbiome should also be investigated to better understand the role of HBM in mediating and priming the infant's immune system. Further, a study of the metabolome of the infant gut and the matching HBM of the mother may identify potential metabolites that could be used as biomarkers for vaccine responses.